Diversity of Echinoderms in Drini Beach Gunung Kidul, Yogyakarta - Mufida, Intan; Pertiwi, Meilisha Putri; Rostikawati, Raden Teti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
Research on the diversity of echinoderms at Drini Beach, Gunung Kidul, Yogyakarta has been conducted from December 2020 to July 2021. This study aimed to determine the Echinoderm diversity index. The method sampling technique used belt transect with determination by purposive sampling with three stations in the intertidal zone based on substrate variations. Station 1 had coral substrate type, station 2 had seagrass substrate type, and sand substrate type for station 3. The sample in this study was the species of Echinoderms found in the station area. After sampling, it obtained 7 species of Echinoderms consisting of 3 classes, classified into 4 orders, and 6 families. The diversity index at all stations is low, followed by a low evenness value and a high dominance value. The species Ophiocoma erinaceus was dominant at stations one and two, while the species Tripneustes gratilla was dominant at stations three. Moreover, the most common habitat for echinoderms is This is due to the availability of abundant food, laying places for echinoderms, and shelter to avoid predators. In addition, it is also supported by temperature, pH, salinity, strong currents, and a good depth for Echinoderm habitat